Effectiveness of Audio-Visual Media in Health Education about Fruits and Vegetables Consumption in Early Adolescents at Palangka Raya Elementary School (Indian Journal of Forensic Medicine & Toxicology, 2020)
Consumption of fruits and vegetables in Indonesia is still lacking (5%), even though fruits and vegetablesplay a role in maintaining the condition of blood pressure, blood sugar and cholesterol levels to prevent noninfectious diseases. One way to increase public awareness to consume fruits and vegetables is through healtheducation. Health education through audiovisual media is considered important because it displays elementsof moving images and sounds that stimulate more senses. This study aims to determine the effectivenessof audiovisual health education media to increase knowledge, attitudes, and behavior of adolescents in theconsumption of vegetables and fruit every day. This research uses quasi experiment method. The sampleof this research is grade 6 students of Menteng State 5, Elementary School in Palangka Raya. The resultsshowed an increase in the proportion of knowledge and good attitude after the intervention period (p-value:0.008 and 0.002). There is no significant relationship between sex with students’ knowledge and attitudestowards vegetable and fruit consumption (p-value: 1.0 and 0.71).
Keywords: fruit and vegetable, knowledge, attitude, gender